A Case of Combined Baclofen and Carisoprodol Withdrawal: The Hidden Dangers of Muscle Relaxants - Rachel P. Sarnoff; Daniel J. Brownstein; Julio Meza; Angela K. Kleiber (Annals of Internal Medicine: Clinical Cases)
Muscle relaxant prescriptions are on the rise for the treatment of chronic pain, although physician education about the effects of overdose, medication interactions, and withdrawal is limited. Simultaneous use of the muscle relaxants baclofen and carisoprodol can result in withdrawal at relatively low doses, possibly because of their synergistic effect. Prior case reports have described withdrawal from either of these muscle relaxants. However, this case report describes the course of a patient who was experiencing withdrawal from both baclofen and carisoprodol. To address such scenarios appropriately, it is important for prescribers to be aware of the withdrawal syndromes associated with these medications.